2010
DOI: 10.2147/ijnrd.s7038
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years of losartan: what have we learned about losartan that can benefit chronic kidney disease patients?

Abstract: Losartan, the first AT1 receptor blocker (ARB), was FDA approved 15 years ago. During those years, researchers and clinicians have developed a growing base of knowledge on the benefits of losartan, particularly for hypertension and renal disease. These benefits include decreasing proteinuria, slowing the progression of diabetic nephropathy, controlling hypertension, and decreasing stroke risk in patients with left ventricular hypertrophy. Although many of the benefits of losartan represent a class effect for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 58 publications
1
25
0
3
Order By: Relevance
“…Biomarker responses shed light on the metabolism and sub-lethal effects of the antihypertensive LOS in a non-target marine organism. The activity of DBF was induced in the gills after 96 h of exposure at 300 ng/L, whereas GST was induced in gills of mussels exposed to 3000 ng/L after 48 h. The metabolism of this pharmaceutical in vertebrates occurs through the Cytochrome P450 (CYP 450) system specifically through the CYP2C9 and CYP3A4 families (Ripley and Hirsch, 2010), which is in agreement with our results obtained in a marine bivalve. Phases I and II of the detoxification system produce reactive oxygen species (ROS) and metabolites, which are able to promote oxidative stress and cellular damages.…”
Section: Nominal Concentration (Ng/l)supporting
confidence: 91%
“…Biomarker responses shed light on the metabolism and sub-lethal effects of the antihypertensive LOS in a non-target marine organism. The activity of DBF was induced in the gills after 96 h of exposure at 300 ng/L, whereas GST was induced in gills of mussels exposed to 3000 ng/L after 48 h. The metabolism of this pharmaceutical in vertebrates occurs through the Cytochrome P450 (CYP 450) system specifically through the CYP2C9 and CYP3A4 families (Ripley and Hirsch, 2010), which is in agreement with our results obtained in a marine bivalve. Phases I and II of the detoxification system produce reactive oxygen species (ROS) and metabolites, which are able to promote oxidative stress and cellular damages.…”
Section: Nominal Concentration (Ng/l)supporting
confidence: 91%
“…Losartan has been shown to reduce vascular resistance of renal arterioles in renal transplant recipients 48 , which may explain the increased cortical perfusion in the LOS+ group. Previous studies have shown renoprotective effects of RAS blockade by losartan, such as reducing proteinuria in diabetic patients and slowing the progression of CKD in non-transplant patients 49 . The current study indicates losartan may provide benefits to allograft recipients as well, and further research of losartan in the context of renal transplantation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, the oral bioavailabilities of the small molecule AT 2 R antagonist, EMA400, and its S ‐enantiomer, EMA401, are similar to that of the AT 1 R antagonist, losartan, in adult male rats , with losartan being used in the clinical setting for the treatment of hypertension in humans . Hence, it is plausible that the oral bioavailability of EMA401 at 33% in the male rat will translate to acceptable oral bioavailability of this compound in humans.…”
Section: Discussionmentioning
confidence: 99%